Implementation of ABC and VED Analysis Methods in Book Inventory Management (Case Study: Toko Buku Al-Madinah) - Hafizhan, Muhamad; Fiatno, Aris (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study aims to evaluate and improve book inventory management at Al-Madinah Bookstore through the application of ABC and VED analysis methods. The ABC method is used to group books based on sales contribution and frequency of use, thus prioritizing the management of the most valuable books. Meanwhile, the VED method is used to classify books based on their level of importance for the continuity of store operations, namely Vital (V), Essential (E), and Desirable (D). This study uses a qualitative approach with descriptive methods to understand the phenomena in the field, while the data is presented and analyzed quantitatively to provide a statistical overview. The analysis results show that the ABC category is divided into 29% category A, 33% category B, and 37% category C, while the VED classification shows 10% of books are Vital, 63% Essential, and 27% Desirable. The ABC method helps prioritize stock control based on sales value, while VED ensures the availability of vital books based on user importance. The synergistic use of these two methods has proven effective in optimizing inventory, minimizing storage costs, and reducing the risk of shortages of important books, thus supporting the Books tore's business sustainability.